2006
DOI: 10.1016/j.jvs.2005.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Reduced lung function in patients with abdominal aortic aneurysm is associated with activation of inflammation and hemostasis, not smoking or cardiovascular disease

Abstract: The association between reduced respiratory function and abdominal aortic aneurysm was not accounted for by cigarette smoking or cardiovascular disease. We hypothesize that activation of inflammation and hemostasis in response to injury may be an important explanation of the association between aneurysm formation and reduced respiratory function. Further studies are required to test this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 33 publications
5
62
0
5
Order By: Relevance
“…Improved understanding of the pathophysiologic mechanisms of remote organ injury might suggest novel therapeutic strategies for decreasing perioperative morbidities [18,19]. In fact, Monsour et al showed that tourniquet-induced limb IR leads to mitochondrial dysfunction in thelung [20].…”
Section: Discussionmentioning
confidence: 99%
“…Improved understanding of the pathophysiologic mechanisms of remote organ injury might suggest novel therapeutic strategies for decreasing perioperative morbidities [18,19]. In fact, Monsour et al showed that tourniquet-induced limb IR leads to mitochondrial dysfunction in thelung [20].…”
Section: Discussionmentioning
confidence: 99%
“…33,34 A host of other risk factors, such as poor lung function, 35 hypertension and high cholesterol levels, 36,37 have been suggested to increase the risk of aneurysmal development, although there are conflicting reports in the current literature. A positive family history, especially in male first-degree relatives, is also associated with increased risk of aneurysm.…”
Section: Other Risk Factorsmentioning
confidence: 99%
“…Wedzicha et al [31] showed that during COPD exacerbations, plasma fibrinogen levels increased and they postulated that this could contribute to abnormal hemostasis and thrombosis, leading to adverse cardiovascular events. Fowkes et al [32] showed increases in circulating D-dimer (breakdown product of fibrin) in subjects with COPD. Hurst et al [33] looked at 36 biomarkers in subjects with COPD exacerbations and showed that plasma CRP concentration, in the presence of a major exacerbation symptom, may be useful in confirming a COPD exacerbation but did not predict exacerbation severity.…”
Section: Systemic Response and Copdmentioning
confidence: 99%